Thrombospondin-1 selectively inhibits early-stage carcinogenesis and angiogenesis but not tumor lymphangiogenesis and lymphatic metastasis in transgenic mice. - Hawighorst, T; Oura, H; Streit, M; Janes, L; Nguyen, L; Brown, L; Oliver, G; Jackson, D; Detmar, M (2002)
The roles played by the endogenous angiogenesis inhibitor thrombospondin-1 (TSP-1) in the early stages of multi-step carcinogenesis and in the control of hematogenous versus lymphatic metastasis are unknown. To investigate these issues we compared tumor development in normal mice and in transgenic mice with targeted overexpression of TSP-1 in the epidermis following a standard two-step chemical skin carcinogenesis regimen. Overexpression of TSP-1 resulted in delayed and reduced development of premalignant epithelial hyperplasias, but did not inhibit the malignant conversion to squamous cell carcinomas. TSP-1 overexpression also suppressed tumor angiogenesis and distant organ metastasis, but failed to inhibit tumor-associated lymphangiogenesis or lymphatic tumor spread to regional lymph nodes. Concomitant with these results, we found that the endothelial TSP-1 receptor CD36 was mostly absent from cutaneous lymphatic vessels. Our findings indicate the potential use of TSP-1 for the prevention of premalignant stages of tumorigenesis and are likely to have implications for the further development of anti-angiogenic cancer therapies.